The under-funding of Latinx-serving school districts. (March 2020) - Baker, Bruce; Cotto, Robert
An analysis of school district spending across the U.S. reveals 66 districts where the students face much greater needs than in surrounding districts (i.e., child poverty is more than 20% higher) but where per-pupil spending is less than 90% of the region's average. This not only means that they have less money to spend on children who require more expensive services and supports, but it also puts them at a competitive disadvantage when it comes to hiring and retaining high-quality teachers and staff from the local area. These districts tend to be located in small to mid-size cities, and they serve disproportionately large numbers of Latinx students .